Computer Breakdown as a Stress Factor during Task Completion under Time Pressure: Identifying Gender Differences Based on Skin Conductance. (23rd October 2013) - Riedl, René; Kindermann, Harald; Auinger, Andreas; Javor, Andrija
Abstract : In today's society, as computers, the Internet, and mobile phones pervade almost every corner of life, the impact of Information and Communication Technologies (ICT) on humans is dramatic. The use of ICT, however, may also have a negative side. Human interaction with technology may lead to notable stress perceptions, a phenomenon referred to as technostress. An investigation of the literature reveals that computer users' gender has largely been ignored in technostress research, treating users as "gender-neutral." To close this significant research gap, we conducted a laboratory experiment in which we investigated users' physiological reaction to the malfunctioning of technology. Based on theories which explain that men, in contrast to women, are more sensitive to "achievement stress, " we predicted that male users would exhibit higher levels of stress than women in cases of system breakdown during the execution of a human-computer interaction task under time pressure, if compared to a breakdown situation without time pressure. Using skin conductance as a stress indicator, the hypothesis was confirmed. Thus, this study shows that user gender is crucial to better understanding the influence of stress factors such as computer malfunctions on physiological stress reactions.